Static electromagnetic field and recombinant human fibroblasts encoding miR-451 and miR-16 increased cell trans-differentiation to CD71+ and CD235a+ erythroid like progenitor - Nafiseh Karoubi; Gholamreza Khamisipour; Nahid Babaei; Narges Obeidi; Abbas Doosti (BioImpacts, 2024)
Introduction: Ex vivo blood production is an urgent need of most countries, and creating production protocols can save the lives of many patients. Despite the recent advances in blood production in ex vivo conditions, its high-scale production is not yet possible, and requires further studies. Therefore, by transfecting fibroblast cells with miR-16, and miR-451 genes, as well as applying low frequency electromagnetic fields (ELF-EMF) treatment, we tried to increase the differentiation of these cells into CD71+ and CD235a+ erythroid like progenitors. Methods: After preparation, and cultivation of human dermal transgenic fibroblast cells, they were transfected by Plenti3-hsa-miR451, Plenti3-hsa-miR16 and Plenti3-backbone inserted into E. coli Stbl4 genome. Then, transgenic fibroblast cells were treated with 10mT ELF-EMF every day for 20 minutes for 7 days. Using a flow cytometer, the expressions of CD71, and CD235a were studied in these cells, and the expressions of genes involved in hematopoiesis were studied using the RT-PCR technique. Results: The results indicated an increase in the differentiation of fibroblast cells treated with 10mT ELF-EMF to erythroid like progenitors. Furthermore, the percentage of CD71+ and CD235a+ cells was the highest in irradiated cells encoding miR-16 and miR-451, which indicates their differentiation into erythroid like progenitors. Also, in the transgenic cells treated with ELF-EMF, an increase in the expressions of α-chain, β-chain, γ-chain and GATA1 genes was observed, which indicates the potential of these cells for hematopoiesis. However, there was no significant difference in the expression of CD34 and CD38 genes in these cell lines. Conclusion: Both ELF-EMF and upregulations of miR-16 and miR-451 lead to improved differentiation of fibroblast cells into erythroid like progenitors.